2009
DOI: 10.1097/jgp.0b013e3181ad4f3c
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic Differences in Beliefs Regarding Alzheimer Disease Among Dementia Family Caregivers

Abstract: Objective The purpose of this study was to examine ethnic differences in female dementia family caregivers’ knowledge, attitudes, and beliefs about Alzheimer disease (AD). Methods Baseline data were collected from 215 female caregivers before their participation in various psychoeducational intervention programs. Caregivers were questioned about the epidemiology, etiology, and treatment of AD. Logistic regressions and one-way analysis of variance were conducted to assess ethnic differences. Results Hispani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
104
3
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 111 publications
(111 citation statements)
references
References 29 publications
3
104
3
1
Order By: Relevance
“…Many individuals and cultures perceive dementiarelated symptoms as a natural part of aging (Ayalon & Arean, 2004;Chow et al, 2002;Eiser & Ellis, 2010;Gelman, 2010;Gray, Jimenez, Cucciare, Tong, & Gallagher-Thompson, 2009;Jett, 2006). For example, Gray et al (2009) asked participants whether the following statement is true: "Significant loss of memory/mental ability, commonly known as senility, is a normal part of aging. "…”
Section: Cultural Differencesmentioning
confidence: 99%
See 2 more Smart Citations
“…Many individuals and cultures perceive dementiarelated symptoms as a natural part of aging (Ayalon & Arean, 2004;Chow et al, 2002;Eiser & Ellis, 2010;Gelman, 2010;Gray, Jimenez, Cucciare, Tong, & Gallagher-Thompson, 2009;Jett, 2006). For example, Gray et al (2009) asked participants whether the following statement is true: "Significant loss of memory/mental ability, commonly known as senility, is a normal part of aging. "…”
Section: Cultural Differencesmentioning
confidence: 99%
“…Numerous cultural differences related to caregiving for patients with AD may also contribute to racial and ethnic disparities (Gray et al, 2009;Napoles et al, 2010). The most frequently documented cultural differences for both African-American and Hispanic caregivers compared with white caregivers are more positive views of caregiving, greater spirituality, a stronger sense of duty to family, and higher value placed on extended family networks (Napoles et al, 2010).…”
Section: Cultural Differencesmentioning
confidence: 99%
See 1 more Smart Citation
“…There is evidence that ethnicity and cross-cultural differences can influence people's understandings of dementia (e.g. Dilworth-Anderson & Gibson, 2002;Gray et al, 2009;Hinton & Levkoff, 1999). Future research could explore illness representations in a more ethnically diverse group of caregivers and consider cross-cultural differences.…”
Section: Discussionmentioning
confidence: 99%
“…Studies exploring caregivers' understandings of dementia have found that caregivers may minimise the seriousness of symptoms by attributing them to ageing (Askham, 1995;Gray, Jimenez, Cucciare, Tong, & Gallagher-Thompson, 2009;Morgan & Laing, 1991), to the person never having had a good memory (Quinn et al, 2008) or to life events (Paton, Johnston, Katona, & Livingston, 2004). Caregivers' beliefs about dementia can influence their understanding of the behaviours they are observing.…”
Section: Introductionmentioning
confidence: 99%